Impact of dopant ratio on the energy harvesting activity of polyaniline modified counter electrodes for Pt‐free dye‐sensitized solar cells. Issue 1 (9th December 2021) - Farooq, Shehna; Bilal, Salma; Tahir, Asif Ali; Shah, Anwar ul Haq Ali
Abstract: Counter electrode (CE) is an essential part of dye‐sensitized solar cells (DSSCs) in determining their efficiency. Ultimately, the high catalytic activity and conductivity of a CE are dependent on the type of electrode material. The utilization of polyaniline (PANI) coatings for surface modification of CE has proven to be worth. Though it is a bit difficult to optimize the efficiency of a polymeric material, a proper combination of inorganic‐organic dopants can impart positive synergistic effects to the resulting PANI in terms of good conductivity, electrocatalytic activity, and low resistance. This work reports on the effect of the combination ration of an organic dopant (ammonium lauryl sulfate, ALS) and an inorganic dopant (sulfuric acid) on the catalytic activity of CEs modified with PANI for DSSCs. The results are compared with those of platinum counter electrode (Pt CE). The maximum conversion efficiency of DSSC with optimized case reaches 4.54%, which is higher than that of Pt counter electrode (4.02%). This organic–inorganic acids doped polymeric material showing an enhanced photoelectrochemical activity might be exploited in the future as a promising material for application in next‐generation solar devices. Abstract : Polyaniline based platinum free dye sensitized solar cell